IMPLEMENTASI PROGRAM PENGENTASAN MASALAH ANAK JALANAN, GELANDANGAN DAN PENGEMIS DI KOTA SEMARANG BERDASARKAN PERDA NO. 5 TAHUN 2014 - Agnesia Indra Sevita; Achmad Taufiq; Soewanto Adhi (Journal of Politic and Government Studies, 2015)
ABSTRACTIONSocial problems are mushrooming in various ways, such as the emergence of street children, vagrants and beggars, especially in big cities becoming the drivers of the formation of policies to alleviate these problems. As well as in the city, the government is required to resolve the social problems of this one with the issue the Regional Regulation No. 5 in 2014 are expected to be able to reduce Persons Social Welfare Society in the city of Semarang. Therefore, how the implementation of programs to alleviate the problems and solutions issued by the Social Service of Semarang in reducing the increase in street children, vagrants, beggars and how to deal with these constraints? This study aim is to give the illustration (description) regarding to the implementation of programs to alleviate social problems, constraints and solutions that provided by the Department of Social Welfare to overcome these obstacles. Data were collected through observation, in-depth interviews, documentation and related research. Qualitative data analysis techniques with analyzing in the form of description, depiction and conclusion on the symptoms studied.                                        From the research, it is known that the problem of street children and the alleviation programs is based on the Regional Regulation of Semarang No. 5 Year 2014. The aim that wanted to be achieved from this program is to provide social assistance, skills training and changed the way of people thinking with a social mindset, in order to live in proper life without having vagrancy or begging for economic demands, and to improve the quality and fairness, in order to improve their social welfare and alleviate social problems. From the discussion, it can be concluded: the alleviation of social problems in this program has been effective and efficient by the standards, objectives, characteristics of enforcement agencies, communication between the implementor, disposition implementor; but the resources, environmental conditions as well as the mindset of the persons which still become the obstacle of the alleviation of this social problem.With the problems of social welfare, in addition to already issued Regulation No. 5 In 2014, the government must implement and enforce these rules well and coordinate with other agencies or institutions concerned. Keywords: ProgramImplementation, Issues Street Children, Vagrants and Beggars, Regional Regulation No.5 In 2014